2019
DOI: 10.1089/ars.2018.7548
|View full text |Cite
|
Sign up to set email alerts
|

NADPH Oxidase 4 Regulates Inflammation in Ischemic Heart Failure: Role of Soluble Epoxide Hydrolase

Abstract: Aims: Oxidative stress is implicated in cardiomyocyte cell death and cardiac remodeling in the failing heart. The role of NADPH oxidase 4 (NOX4) in cardiac adaptation to pressure overload is controversial, but its function in myocardial ischemic stress has not been thoroughly elucidated. This study examined the function of NOX4 in the pathogenesis of ischemic heart failure, utilizing mouse models, cell culture, and human heart samples. Results: Nox4-/mice showed a protective phenotype in response to permanent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 78 publications
3
22
1
Order By: Relevance
“…In particular, NOX4‐derived ROS is important for the survival of many cancer types . However, recent reports have suggested that NOX4 activity perturbs redox balance in cells, resulting in cell death . These reports are consistent with our result that NOX4 inhibition finally blocked the PS exposure and DNA fragmentation of Entamoeba ‐stimulated Jurkat T cells.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In particular, NOX4‐derived ROS is important for the survival of many cancer types . However, recent reports have suggested that NOX4 activity perturbs redox balance in cells, resulting in cell death . These reports are consistent with our result that NOX4 inhibition finally blocked the PS exposure and DNA fragmentation of Entamoeba ‐stimulated Jurkat T cells.…”
Section: Discussionsupporting
confidence: 92%
“…In an ischaemic heart failure model, NOX4 directly increases cardiomyocyte death. Moreover, cardiomyocyte death was reduced in a NOX4 knockout mice, whereas cell death was increased by NOX4 overexpression . In addition, it has been reported that human retinal endothelial cells treated with high glucose induce NOX4‐derived ROS and eventually increase cell death .…”
Section: Discussionmentioning
confidence: 98%
“…Importantly, the expression of sEH in ligation hearts was significantly greater than that in hearts from wild-type mice. In addition, the inflammation factors were ameliorated when treated with sEH inhibitors ( Stevenson et al, 2019 ). In another HF model induced by LPS, the cardiac function was decreased, as evaluated by hemodynamic analysis and echocardiography, while sEH deficiency attenuated LPS-induced cardiac dysfunction.…”
Section: The Role Of Eets In the Pathological Changes Of Cardiac Remomentioning
confidence: 99%
“…Stevenson et al found that CCL5 level increased significantly in the human hearts with ischemic cardiomyopathy compared to control nonfailing hearts. 32 What’s more, Montecucco et al reported that the incidence of postinfarct heart failure was significantly reduced by treatment with anti-CCL5 mAb in chronic cardiac ischaemia mouse models. 27 These findings show that CCL5 play an important role in the process of IHF and NIHF.…”
Section: Discussionmentioning
confidence: 99%